Oriented Thiophene‐Extended Benzotrithiophene Covalent Organic Framework Thin Films: Directional Electrical Conductivity. (24th August 2022) - Frey, Laura; Pöhls, Jonas Fredrik; Hennemann, Matthias; Mähringer, Andre; Reuter, Stephan; Clark, Timothy; Weitz, Ralf Thomas; Medina, Dana Dina
Abstract: The synthesis of covalent organic frameworks (COFs) based on a novel thiophene‐extended benzotrithiophene (BTT) building block is described, which in combination with triazine‐based amines (1, 3, 5‐triazine‐2, 4, 6‐triyl)trianiline (TTA) or (1, 3, 5‐triazine‐2, 4, 6‐triyl)tris(([1, 1´‐biphenyl]‐4‐amine)) (TTTBA)) affords crystalline, and porous imine‐linked COFs, BTT TTA and BTT TTTBA, with surface areas as high as 932 and 1200 m 2 g −1, respectively. Oriented thin films are grown successfully on different substrates, as indicated by grazing incidence diffraction (GID). Room‐temperature in‐plane electrical conductivity of up to 10 −4 S m −1 is measured for both COFs. Temperature‐dependent electrical conductivity measurements indicate activation energies of ≈123.3 meV for BTT TTA and ≈137.5 meV for BTT TTTBA and trap‐dominated charge transport via a hopping mechanism for both COFs. Moreover, conductive atomic force microscopy reveals directional and defect‐dominated charge transport in the oriented BTT COF films with a strong preference for the in‐plane direction within the molecular 2D‐planes. Quantum mechanical calculations predict BTT TTTBA to conduct holes and electrons effectively in both in‐plane and out‐of‐plane directions. In‐plane, charge carrier transport is of hopping character where the triazine cores represent the barrier. Out‐of‐plane, a continuous charge‐carrier pathway is calculated that is hampered by an imposed structural defect simulated by a rotated molecular COF layer. Abstract : Charge carrier migration in covalent organic frameworks (COFs) is a key aspect for their incorporation in advanced applications. To utilize COFs as devices, unraveling COFs' conductive pathways and mechanisms is vital. The synthesis of novel electroactive thiophene‐extended benzotrithiophene‐based COFs, their overall electrical conductivity is determined and the different paths for charge carrier migration are clarified.